2007
DOI: 10.1111/j.1538-7836.2007.02592.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐hematopoietic EPCR regulates the coagulation and inflammatory responses during endotoxemia

Abstract: Summary Background: Activated protein C (APC) protects the host from severe sepsis. Endothelial protein C receptor (EPCR) is expressed on both hematopoietic leukocytes and non‐hematopoietic endothelium, and plays a key role in protein C activation.Objectives: We explore the influence of EPCR deletion on the responses to lipopolysaccharide (LPS) and then determine whether the observed differences are due to loss of hematopoietic or non‐hematopoietic EPCR.Methods and results: After LPS challenge, EPCR null (Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 42 publications
4
48
2
Order By: Relevance
“…Thus, in our monocyte model, the upregulation of IL-10 by recombinant activated protein C appears to be independent of EPCR. Consistent with this finding, studies by Zheng et al (49) demonstrated that deficiency of EPCR in nonhematopoietic cells (i.e., vascular endothelial cells) exaggerated the host responses to LPS, whereas deficiency of EPCR in hematopoietic leukocytes played a much less important role (49). Furthermore, recent reports demonstrate that recombinant activated protein C can induce a cell signaling response via ERK activation through a PAR-1/S1P1-dependent, but EPCR-independent, mechanism (50).…”
Section: Figuresupporting
confidence: 71%
“…Thus, in our monocyte model, the upregulation of IL-10 by recombinant activated protein C appears to be independent of EPCR. Consistent with this finding, studies by Zheng et al (49) demonstrated that deficiency of EPCR in nonhematopoietic cells (i.e., vascular endothelial cells) exaggerated the host responses to LPS, whereas deficiency of EPCR in hematopoietic leukocytes played a much less important role (49). Furthermore, recent reports demonstrate that recombinant activated protein C can induce a cell signaling response via ERK activation through a PAR-1/S1P1-dependent, but EPCR-independent, mechanism (50).…”
Section: Figuresupporting
confidence: 71%
“…The role of EPCR as a crucial co-receptor for PC activation and aPC-mediated cytoprotective signaling in vascular and immune cells is supported by in vitro and in vivo data (57)(58)(59)(60)(61)(62)(63). However, TF is normally not expressed in the vascular endothelium but co-expressed with EPCR in extravascular cells.…”
Section: Discussionmentioning
confidence: 74%
“…However, the mechanism underlying its antiinflammatory function is poorly understood, particularly in regard to the involvement of its receptor, EPCR (12,(14)(15)(16)(17)(18). Here, we report our evidence, using LPS-induced lethal endotoxemia as a model of sepsis in mice, that the efficacy of APC as an effective antiinflammatory agent toward activated macrophages is critically dependent on integrin CD11b/CD18.…”
Section: Introductionmentioning
confidence: 74%